Effects of rhizobacteria on the biology and behavior of Plutella xylostella (Lepidoptera: Plutellidae) - Thomaz Thuler, Robson; Iost Filho, Fernando Henrique; Charlo, Hamilton César De Oliveira; De Bortoli, Sergio Antônio [UNESP] (SAGE Publications, 2017)
Plant induced resistance is a tool for integrated pest management, aimed at increasing plant defense against stress, which is compatible with other techniques. Rhizobacteria act in the plant through metabolic changes and may have direct effects on plant-feeding insects. The objective of this study was to determine the effects of cabbage plants inoculated with rhizobacteria on the biology and behavior of diamondback moth, Plutella xylostella (Lepidoptera: Plutellidae). Cabbage seeds inoculated with 12 rhizobacteria strains were sowed in polystyrene trays and later transplanted into the greenhouse. The cabbage plants with sufficient size to support stress were then infested with diamondback moth caterpillars. Later, healthy leaves suffering injuries were collected and taken to the laboratory to feed P. xylostella second instar caterpillars that were evaluated for larval and pupal viability and duration, pupal weight, and sex ratio. The reduction of leaf area was then calculated as a measure of the amount of larval feeding. Non-preference for feeding and oviposition assays were also performed, by comparing the control treatment and plants inoculated with different rhizobacterial strains. Plants inoculated with the strains EN4 of Kluyvera ascorbata and HPF14 of Bacillus thuringiensis negatively affected the biological characteristics of P. xylostella when such traits were evaluated together, without directly affecting the insect behavior.
Efectos de rizobacteriasen la biología y comportamiento de plutella xylostella (Lepidoptera: Plutellidae)
Keywords: Brassica; Diamondback moth; Integrated pest management